Preface [Intelligent Technologies for Interactive Entertainment] - Cortez, Paulo (2019)
[Excerpt] The business goal in healthcare is to increase the quality of services in healthcare and thus reduce costs. This objective contributes to improving the quality of life of patients, in some cases reducing mortality and morbidity. To achieve this goal, the use of intelligent systems in the decision-making process becomes essential. The workshop was focused on demonstrating how to take advantage of using computational intelligence, ensuring interoperability and security, and overcoming local and temporal barriers in order to support society’s needs and the development of innovative systems and applications to support healthcare decision making. In this workshop, innovative and exciting works were presented, and the discussion about how intelligent systems can contribute to improving the quality of the decision process in healthcare was promoted. This workshop involved several topics associated with business informatics when applied to healthcare (image processing, clustering, geographic information system, logic programming, and case-based reasoning and natural language). These works represent an interesting focus of research. Eight papers were submitted and five of them were accepted for presentation. [...]